ответьте подалуйст правильн с не получается

Nzzjsjs Nzzjsjs    1   29.04.2020 10:05    0

Ответы
VikaPika561 VikaPika561  14.10.2020 02:03

Пошаговое объяснение:

81*3^{-3}=3^4*3^{-3}=3\\16*(2^{-3})^2=2^4*2^{-6}=2^{-2}=\frac{1}{4}\\5^-^6*5^8:125=5^2:5^3=5^{-1}=\frac{1}{5}\\36^{-1}*(\frac{1}{6})^{-4}=6^{-2}*6^4=6^2=36\\32^{-2}*4^4=2^{-10}*2^8=2^{-2}=\frac{1}{4}\\27^{-2}:9^{-4}=3^{-6}:3^{-8}=3^2=9\\\frac{7^{-6}*7^{-6}}{(-7)^{-13}}=-\frac{7^{13}}{7^1^2}=-7

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика